Antimicrobial Potential of Calotropis gigantea Leaf Against Klebsiella pneumoniae in Ventilator-Associated Pneumonia - Teuku Zulfikar; Tongku N. Siregar; Anna Rozaliyani; Amalia Sutriana (Journal of Human, Earth, and Future)
Calotropis gigantea or biduri has traditional medicinal properties. However, the effect of C. gigantea leaves in assisting the function of antibiotic-resistant ventilator-associated pneumonia (VAP), particularly caused by Klebsiella pneumoniae, has not been evaluated. The purpose of this study was to identify the active compounds of C. gigantea leaf extracts growing in the coastal area of Alue Naga, Banda Aceh, Indonesia, and assess its antimicrobial potential in preventing microbial resistance. C. gigantea leaves were extracted using three different solvents: ethanol, ethyl acetate, and n-hexane. The three extracts of C. gigantea leaves were analyzed for antioxidant activity using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, and the active compounds of C. gigantea were identified using gas chromatography-mass spectroscopy (GC-MS). The dominant bioactive compounds of the C. gigantea extract were enrolled for molecular docking analysis. The results of this study showed that the inhibitory concentration 50% (IC50) of the ethanol extract had a higher antioxidant activity (IC50 value of 3.3 ppm) than the ethyl acetate (IC50 value of 22.97 ppm) and n-hexane (IC50 value of 32.9 ppm). Bioactive compound identification using GC-MS from the three extracts showed similar dominant compounds, which were α-amyrin and lup-20(29)-en-3-ol, and these compounds belonged to the class of triterpenoid derivative compounds. Molecular docking analysis showed that α-amyrin (-9.6 Kcal/mol), β-amyrin (-9.6 Kcal/mol), and epilupeol (-9.2 Kcal/mol) in C. gigantea leaves had higher binding free energy values compared to cefixime (-8.7 Kcal/mol). Thus, it could be concluded that C. gigantea leaf extract is assumed to have great potential as an antimicrobial agent and in preventing microbial resistance, particularly in cases of VAP caused by Klebsiella pneumoniae.